Penguatan Kapasitas UMKM Rempeyek Mangkok melalui Pelatihan dan Pendampingan Digital Marketing, HPP, dan Laporan Keuangan: Strengthening the Capacity of Rempeyek Mangkok MSMEs through Training and Assistance in Digital Marketing, Cost of Goods Sold, and Financial Reporting - Hariyanto, Wiwit; Erma Widiana, Muslichah; Mulyadi, Mulyadi; Kholidah, Naila Najwa; Andrian, Gilang Januar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service activity was carried out at the Rempeyek Mangkok MSME, located in the Bumi Gedangan Indah Housing Complex, Block C9, Gedangan, Sidoarjo. The purpose of this community service activity was to increase the marketing capacity of MSMEs through digital marketing and social media, as well as to provide understanding and training in calculating COGS and preparing financial reports. The community service team’s activities included planning, implementation, and evaluation. The results of the activity showed an increase in business owners’ skills in using digital platforms to expand markets, as well as a better understanding of production cost management and financial recording, and their application. The implication of this activity is the creation of MSMEs that are more professional, better adapted to technological developments, and more competitive in the digital market. The impact of this Community Service program is seen in the increased skills of Rempeyek Mangkok MSME owners in using marketplaces and social media as marketing tools, as well as in their ability to create simple financial reports and calculate the Cost of Goods Sold (COGS) more accurately. This impacts more accurate, competitive product pricing and opens up wider market opportunities. Overall, this activity enhances the professionalism and competitiveness of Rempeyek Mangkok MSMEs and strengthens economic capacity.